Non-alcoholic fatty liver disease and vascular disease - Forlano,R; Mullish,BH; Nathwani,R; Dhar,A; Thursz,MR; Manousou,P (Current Vascular Pharmacology, 2020)
Non-Alcoholic Fatty Liver Disease (NAFLD) represents an increasing cause of liver disease worldwide. However, notably, the primary cause of morbidity and mortality in patients with NAFLD is cardiovascular disease (CVD), with fibrosis stage being the strongest disease-specific predictor. It is globally-projected that NAFLD will become increasingly prevalent, especially among children and younger adults. As such, even within the next few years, NAFLD will contribute considerably to the overall CVD burden. In this review, we discuss the role of NAFLD as an emerging risk factor for CVD. In particular, this article aims to provide an overview of pathological drivers of vascular damage in patients with NAFLD. Moreover, the impact of NAFLD on the development, severity and the progression of subclinical and clinical CVD will be discussed. Finally, the review illustrates current and potential future perspectives for screening for CVD in this high-risk population.